2003
DOI: 10.1001/archopht.121.10.1415
|View full text |Cite
|
Sign up to set email alerts
|

Nonmechanical Q-Switched Erbium:YAG Laser Trephination for Penetrating Keratoplasty

Abstract: To assess the alterations in human donor corneal tissue induced by Q-switched erbium (Er):YAG laser corneal trephination. Methods: Thirty human corneoscleral donor buttons unsuitable for transplantation were placed in an artificial chamber on an automated rotation device. Corneas were trephined with a Q-switched Er:YAG laser (wavelength, 2.94 µm; pulse duration, 400 nanoseconds) along (donor and recipient) aluminum silicate (ceramic) open masks. A spot diameter of 0.65 mm, energy setting of 50 mJ/pulse, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They reported the thermal effect in the form of band of carbonization and a coagulation zone associated with collagen and cellular damage. [ 22 ] Jones et al . reported a smooth surface architecture of FS-assisted trephined corneas using scanning electron microscopic.…”
Section: Discussionmentioning
confidence: 99%
“…They reported the thermal effect in the form of band of carbonization and a coagulation zone associated with collagen and cellular damage. [ 22 ] Jones et al . reported a smooth surface architecture of FS-assisted trephined corneas using scanning electron microscopic.…”
Section: Discussionmentioning
confidence: 99%
“…Five years ago, one group studied the alterations induced by a Q-switched erbium YAG laser (nanosecond pulsed laser) during corneal trephination. 25 Light and transmission electron microscopy revealed thermal side effects, which consisted of a carbonization band measuring 1.2 to 6.5 mm wide and a larger coagulation zone with collagen and cellular damage. Recently, a study reported scanning electron microscopy of femtosecond laser trephinations on eye bank eyes showing smooth surface architecture.…”
Section: Discussionmentioning
confidence: 99%